مقارنة بعض الطرائق المعلمية واللامعلمية لتصميم القطاعات العشوائية للقياسات المكررة - رشيد, ظافر حسين; حسين, سجى محمد (Journal of Economics and Administrative Sciences, 2007)
The repeated measurement design is called a complete randomized block design for repeated measurement when the subject is given the all different treatments , in this case the subject is considered as a block . Many of nonparametric methods were considered like Friedman test (1937) and Koch test(1969) and Kepner&Robinson test(1988) when the assumption of normal distribution of the data is not satisfied .as well as F test  when the assumptions of the analysis of variance is satisfied ,where the observations within blocks are assumed to be equally correlated . The purpose of this paper is to summarize the result of the simulation study for comparing these methods as well as present the suggestedMethod and compare their results .